Is Symptom Screening Useful for Identifying COVID-19 Infection in School Settings? Georgia, USA. (December 2021) - Swanson, Megan; Hast, Marisa; Burnett, Eleanor; Oraka, Emeka; Kimball, Anne; Morris, Elana; Marcet, Paula L.; Almendares, Olivia; Franklin, Rachel; Mehari, Lemlem; McCloud, Jazmyn; Kirking, Hannah L.; et al.
This study's goal was to characterize the utility of symptom screening in staff and students for COVID-19 identification and control of transmission in a school setting. We conducted a secondary analysis of cross-sectional data for staff, students and associated household members in a Georgia school district exposed to COVID-19 cases who received RT-PCR testing and symptom monitoring. Among positive contacts, 30/49 (61%) of students and 1/6 (17%) of staff reported no symptoms consistent with COVID-19. Symptom sensitivity was 30% in elementary students and 42% in middle/high students. Fifty-three percent (10/19) of symptomatic positive contacts had at least one household member test positive for SARS-CoV-2 compared with 50% (10/20) of asymptomatic positive contacts. The absence of symptoms in children is not indicative of a lack of SARS-CoV-2 infection or reduced risk of infection for associated household members. Testing all close contacts of people with COVID-19 in schools is needed to interrupt transmission networks.